Post-Anthesis Drought Management in Late-Shown Wheat (Triticum aestivum) - Bhari, Pramod; Sah, Shrawan K (Journal of Agriculture and Environment, 2013)
Post anthesis drought is common problem in late sown wheat, which reduces crop yield. A field experiment was conducted at Institute of Agriculture and Animal Science (IAAS), Rampur in 2005/06 to find out the effect of irrigation, seed rate and mulch on soil moisture content and productivity of late sown wheat. Irrigation applied at crown root initiation CRI and heading stage significantly increased moisture content at 80 days after sowing, grain filling period (GFP) and crop duration period (CDP), thousand grain weight, grain yield and harvest index. Higher seed rate was non significant on yield attributes and yield. Soil moisture content at 30, 80 and 95 days after sowing, vegetative growth period (VGP) and crop duration period, and grain yield were significantly higher in mulched plot than non mulched plot. Irrigation at reproductive stage and mulch were effective in increasing yield of late sown wheat.